Febrile seizures: a population‐based study - Juliane S. Dalbem; Heloise H. Siqueira; Mariano M. Espinosa; Regina P. Alvarenga (Brazilian Society of Pediatrics, 2015)
Objectives: To determine the prevalence of benign febrile seizures of childhood and describe the clinical and epidemiological profile of this population. Methods: This was a population‐based, cross‐sectional study, carried out in the city of Barra do Bugres, MT, Brazil, from August of 2012 to August of 2013. Data were collected in two phases. In the first phase, a questionnaire that was previously validated in another Brazilian study, was used to identify suspected cases of seizures. In the second phase, a neurological evaluation was performed to confirm diagnosis. Results: The prevalence was 6.4/1,000 inhabitants (95% CI: 3.8‐10.1). There was no difference between genders. Simple febrile seizures were found in 88.8% of cases. A family history of febrile seizures in first‐degree relatives and history of epilepsy was present in 33.3% and 11.1% of patients, respectively. Conclusions: The prevalence of febrile seizures in Midwestern Brazil was lower than that found in other Brazilian regions, probably due to the inclusion only of febrile seizures with motor manifestations and differences in socioeconomic factors among the evaluated areas.